Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1542/peds.2006-1505
|View full text |Cite
|
Sign up to set email alerts
|

Families' Health-Related Social Problems and Missed Referral Opportunities

Abstract: Urban children and families reported a significant burden of health-related social problems yet infrequent pediatric screening or referral for these problems. Of families who reported receiving referrals, a majority contacted the recommended agencies and found them helpful. This study also demonstrates the feasibility of using a computer-based questionnaire to identify health-related social problems in a routine outpatient clinic setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
141
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(167 citation statements)
references
References 28 publications
7
141
0
6
Order By: Relevance
“…29 These all point to the need for systematic comprehensive social screening in pediatric health care settings. 30 Rates of such screening are low, even in settings serving lowincome populations where social adversities are more prevalent. [30][31][32] Informal social screening is inadequate: providers routinely underestimate social needs in most areas except drug and alcohol use, 33 and standardized screening has been shown to be more sensitive than provider clinical interviews.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 These all point to the need for systematic comprehensive social screening in pediatric health care settings. 30 Rates of such screening are low, even in settings serving lowincome populations where social adversities are more prevalent. [30][31][32] Informal social screening is inadequate: providers routinely underestimate social needs in most areas except drug and alcohol use, 33 and standardized screening has been shown to be more sensitive than provider clinical interviews.…”
Section: Discussionmentioning
confidence: 99%
“…30 Rates of such screening are low, even in settings serving lowincome populations where social adversities are more prevalent. [30][31][32] Informal social screening is inadequate: providers routinely underestimate social needs in most areas except drug and alcohol use, 33 and standardized screening has been shown to be more sensitive than provider clinical interviews. 34 One obstacle to social and economic needs screening is potential patient discomfort in reporting what may be sensitive or stigmatized conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In lieu of having an on-site care navigator or social worker, practices might consider compiling or identifying a list of community resources to have available; doing so could allow for quick and targeted interventions during the child's appointment. 59 To develop or identify such a list, practices may work with a family advisory group to identify the most pertinent needs and resources. Alternatively, practices can turn to their local AAP chapter, health plans, hospitals, or nonprofit organizations that may already have existing and updated lists.…”
Section: Compiling a Resource Directorymentioning
confidence: 99%
“…Some pediatricians may direct families to programs that reduce the impact of poverty on child and maternal nutrition and health care, and connect parents with social services and community resources to address family needs related to poverty, such as housing, employment, and affordable child care. 58 Parent-reported screening tools for assessment and referral of povertyrelated concerns have been developed and tested for use in WCC, 60,61 but none have been widely adopted, and studies suggest that these social concerns are usually not elicited during WCC visits. A study of parents in 2 urban pediatric clinics found that, although 82% of families reported having at least 1 psychosocial family concern (eg, housing, food, income insecurity), nearly one-half also reported having at least 1 unmet referral need.…”
Section: Povertymentioning
confidence: 99%
“…A study of parents in 2 urban pediatric clinics found that, although 82% of families reported having at least 1 psychosocial family concern (eg, housing, food, income insecurity), nearly one-half also reported having at least 1 unmet referral need. 61 …”
Section: Povertymentioning
confidence: 99%